Back to basics in COVID‐19: Antigens and antibodies—Completing the puzzle. Issue 10 (18th March 2021) - Neagu, Monica; Calina, Daniela; Docea, Anca Oana; Constantin, Carolina; Filippini, Tommaso; Vinceti, Marco; Drakoulis, Nikolaos; Poulas, Konstantinos; Nikolouzakis, Taxiarchis Konstantinos; Spandidos, Demetrios A.; Tsatsakis, Aristidis
Abstract: The outbreak of the coronavirus disease 2019 (COVID‐19) has gathered 1 year of scientific/clinical information. This informational asset should be thoroughly and wisely used in the coming year colliding in a global task force to control this infection. Epidemiology of this infection shows that the available estimates of SARS‐CoV‐2 infection prevalence largely depended on the availability of molecular testing and the extent of tested population. Within molecular diagnosis, the viability and infectiousness of the virus in the tested samples should be further investigated. Moreover, SARS‐CoV‐2 has a genetic normal evolution that is a dynamic process. The immune system participates to the counterattack of the viral infection by pathogen elimination, cellular homoeostasis, tissue repair and generation of memory cells that would be reactivated upon a second encounter with the same virus. In all these stages, we still have knowledge to be gathered regarding antibody persistence, protective effects and immunological memory. Moreover, information regarding the intense pro‐inflammatory action in severe cases still lacks and this is important in stratifying patients for difficult to treat cases. Without being exhaustive, the review will cover these important issues to be acknowledged to further advance in the battle against the current pandemia.